Primary Prevention of Cardiovascular Disease - Danny J. Eapen, MD (Cardiovascular Innovations and Applications, 2016)
Cardiovascular disease (CVD) is the leading cause of death worldwide. This article focuses on current guidelines for the primary prevention of CVD and addresses management of key risk factors. Dietary modification, weight loss, exercise, and tobacco use cessation are specific areas where focused efforts can successfully reduce CVD risk on both an individual and a societal level. Specific areas requiring management include dyslipidemia, hypertension, physical activity, diabetes, aspirin use, and alcohol intake. These preventive efforts have major public health implications. As the global population continues to grow, health care expenditures will also rise, with the potential to eventually overwhelm the health care system. Therefore it is imperative to apply our collective efforts on CVD prevention to improve the cardiovascular health of individuals, communities, and nations.